Enhancing Employee Performance through Servant Leadership: A Quantitative Study in a Jakarta-Based Technology Firm - Ferrianto, Patricia Aletha; Munthe, Rusli Ginting (Lentera Ilmu Nusantara, 2025)
This study aims to analyze the impact of servant leadership on employee performance at PT X, a technology company operating under a B2B2C business model in Jakarta, Indonesia. Employing a quantitative approach, the research involved 102 respondents from a total population of 130 employees, selected using the Isaac and Michael table. Data were collected through a questionnaire rigorously tested for validity and reliability, and analyzed using normality tests and simple regression analysis. The findings reveal that servant leadership positively influences employee performance by 17.6%. The respondent profile indicates that the majority are aged 25–28 years, hold a bachelor's degree, and have no children. The highest indicator of servant leadership is the manager's emphasis on collective well-being, scoring 4.03, while the highest indicator of employee performance is openness to new ideas and suggestions, scoring 4.43. This study provides managerial implications for enhancing leadership practices to support employee performance in technology-driven companies. Theoretically, this study contributes to the growing body of research on servant leadership by empirically validating its influence on employee performance within the context of a modern B2B2C technology firm, addressing a gap in literature related to leadership effectiveness in digitally oriented organizational models.